Sustainable economic growth in the European Union under COVID-19 conditions - Rūta Banelienė (Contemporary Economics, 2022)
All countries of the European Union (EU) have had their economies impacted by COVID-19 and should focus their efforts on managing the negative impacts on their GDP growth. Since EU countries vary considerably in many criteria, the same policy would not fit all EU countries. This paper analyzes how sustainable economic growth could be maintained in the long run while considering three criteria, including R&D investment, gross value added per employee and country size by population; and which factors could have the highest impacts on economic growth in the recovery process according to supply and demand. Countries were examined according to the mentioned criteria by applying the panel least squares method. The major estimation outputs show the stronger effect of the supply side on economic growth, the higher role of human capital in small EU countries where R&D investment exceeds 3% of GDP, and the critical effect of exports on GDP growth in the large EU countries with the lowest R&D investment. This segment depends the most on smooth exports of goods and service flows and could be the most vulnerable under COVID-19 conditions. Therefore, seeking to keep economic growth on track, EU countries should use different strategies and fiscal measures depending on the most vulnerable factors for their economic growth. In addition, this is the right time to revise values of economic growth, and governments should be more focused on the recovery of their economies on the sustainable development goals (SDGs) agenda.
Keywords: A10; C23; E17; F01; F39; F63; O39; O40; 330; GDP growth; European Union countries; R&D investment; employment; exports